Epidemiology of Stomach Cancer in Northeastern States of India: Focusing on Nagaland and the Effectiveness of Screening Programs - Atul Khajuria (International Journal of Pathogens, 2025)
Stomach cancer represents a critical public health burden in northeastern India, with Nagaland exhibiting the highest age-standardized incidence rate in the country - nearly triple the national average. This elevated risk profile stems from multiple factors including traditional dietary practices (high consumption of smoked meats and fermented foods), widespread Helicobacter pylori infection (affecting approximately 70% of adults), prevalent tobacco/alcohol use, and limited healthcare infrastructure. Despite demonstrated success of endoscopic screening programs in nations like Japan and South Korea, such initiatives remain largely unavailable in Nagaland, creating a pressing need to examine both epidemiological patterns and screening barriers in this high-risk population.
Keywords: Helicobacter pylori; India; cancer epidemiology; cancer screening; early detection of cancer; gastric cancer; health disparities; public health